2000
DOI: 10.1507/endocrj.47.91
|View full text |Cite
|
Sign up to set email alerts
|

DiGeorge Syndrome with Graves' Disease. A Case Report.

Abstract: Abstract.DiGeorge syndrome (DGS) is characterized by aplasia or hypoplasia of the thymus and parathyroid glands, cardiac defects and anomaly face. This syndrome is usually associated with hypocalcemia resulting from hypoparathyroidism.In most cases the initial symptom is tetany caused by hypocalcemia within 24-48 hours after birth, with symptoms by immune abnormality appearing later. We report a woman who passed with no symptoms before age 18 and was diagnosed DiGeorge syndrome by tetany with developing auto-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
(3 reference statements)
1
16
0
2
Order By: Relevance
“…Graves’ disease has been reported to be associated with chromosome 22q11.2 microdeletion syndrome, indicating that the individuals with this syndrome have a predisposition to autoimmune diseases [13, 14]. We also observed 2 cases developing autoimmune thyroid disorders such as Hashimoto thyroiditis and Graves’ disease.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Graves’ disease has been reported to be associated with chromosome 22q11.2 microdeletion syndrome, indicating that the individuals with this syndrome have a predisposition to autoimmune diseases [13, 14]. We also observed 2 cases developing autoimmune thyroid disorders such as Hashimoto thyroiditis and Graves’ disease.…”
Section: Discussionsupporting
confidence: 54%
“…In previous studies, hypocalcemia, due to the abnormal parathyroid function, was reported to be the most common endocrine abnormality [7,8,9,10,11,12]. In addition, Graves’ disease is occasionally associated with this syndrome, in conjunction with the susceptibility to autoimmune diseases [13, 14]. The incidence of short stature associated with 22q11.2 microdeletion syndrome ranges from 39 to 67% [15], but no correlation has been found between growth hormone levels and this syndrome [8, 15].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the development of thyrotoxicosis in DiGeorge syndrome is unclear, but several reports have demonstrated the presence of thyroid antibodies, findings that indicate a likely autoimmune etiology (9,10 ). Paradoxically, these patients with a reduced immune function thus appear to develop likely autoimmune-mediated thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other auto-immune diseases have been observed in patients with a 22q11 microdeletion (Table 1). Four cases of auto-immune thyroid disease (Graves disease) have been described [1,10,11]. Pinchas et al [17] observed in a 5-year-old girl with DGS, a liver disease with epitheliod granulomata, smooth muscle Study showed decreased lifespan and splenic sequestration antibodies and mononuclear cell infiltrate supporting the diagnosis of granulomatous hepatitis, of probable auto-immune origin.…”
Section: Discussionmentioning
confidence: 99%
“…Now, this concept is not sufficient to embrace all the phenotypic forms of the 22q11 microdeletion -the term ''22q11.2 deletion syndrome'' is now widely used [2,15,19]. A few observations of auto-immune disorders have been reported in patients with the 22q11 deletion [1,3,8,11,13,17,18]. To the best of our knowledge, six observations of auto-immune cytopenia have been reported in the literature [1,3,13,17].…”
Section: Introductionmentioning
confidence: 99%